The teachers' standards in the classroom - Blatchford, Roy (Sage, 2015)
This second edition has been updated to include notes on the new OFSTED framework and the new National Curriculum. Also included are more questions to help trainee teachers think around the standards in relation to placements and assess how and whether they have met the requirements.